Resilient Waterfront Architecture And Planning To Curb Urban Sprawl Along Water Bodies – The Case Of Weija Reservoir, Ghana - Boateng, Cornelius Kyei; Quagraine, Kwamena Akraba; Quagraine, Victor Kwesi (MAJ - Malaysia Architectural Journal, 2025)
Urban sprawl is a problem that has generated a lot of debate in policy-making and the academic sector. The degradation of green areas, an outcome of urban sprawl, is identified as one of the issues affecting the natural ecosystem. Studies show that reserved lands meant to protect water bodies continue to face deterioration due to uncontrolled development. After its creation in 1977, the Weija Reservoir has been facing encroachment due to rapid urbanisation in its surrounding environment. The pragmatism worldview drove this research to determine the encroachment issues by urban sprawl on riparian vegetation of the Weija reservoir. With the aid of Geographic Information Systems (GIS) and remote sensing technology, the designated buffer for the Weija reservoir was mapped for the Ga-South Municipality - Ghana, within which a more significant portion of the reservoir is. The study observed available satellite data for 1991, 2017, and 2021. The study observed that about 13% of the Weija reservoir’s buffer(per requirements) had been encroached on by settlements by 2021. The reasons for the encroachment of the Weija reservoir’s buffer raised from the study were the lack of collaboration among the various stakeholders within the reservoir’s use and management framework. The research explored using urban design principles to develop resilient proposals for the selected site to improve the ecological and aquatic lives of the people at the Weija waterfront. The study findings concluded that the management of wetlands in Ghana should take a turn; various stakeholders should educate communities to participate in decisions concerning waterfront developments, and stakeholder collaborations should be enhanced.